Demands, responsibility, and influence in Malawi's participatory agricultural extension services. Issue 1 (2nd January 2018) - Álvarez-Mingote, Cristina; McNamara, Paul E.
ABSTRACT: Participatory governance offers the potential to deliver responsive and accountable services. This article tests this expectation by looking at how members of participatory extension platforms in Malawi understand the meaning of "demand-driven" services, and allocate responsibility and influence in service provision. Results show that most respondents agree on bottom-up extension services that respond to expressed farmers' needs (86% of respondents), and assign responsibility and influence widely across state and non-state actors. While these findings suggest that these participatory mechanisms can promote responsiveness to farmers' needs and accountability, they also point toward different governance challenges in extension services.